IMMUNOHISTOCHEMICAL EXPRESSION OF HORMONE RECEPTORS AND HER-2/neu IN CARCINOMA BREAST: A CORRELATION STUDY - KALAIVANI AMITKUMAR; S.JAYANTHI; D.KADAMBARI (International Journal of Pharma and Bio Sciences, 2013)
Incidence of breast cancer is increasing in developing countries. The chances of cure are related to early diagnosis. In recent years there has been increased use of core needle biopsy for preoperative diagnosis of breast lesions. Seventy one patients, who were diagnosed to have infiltrating ductal carcinoma on fine needle cytology and for whom core needle biopsy was done were taken up for the study. A detailed histopathological examination and immunohistochemical profile using the antibodies against estrogen receptors(ER), progesterone receptors (PR) and HER-2/neu were done. Finally, histological grade, clinical stage and immunohistochemical profile were correlated with each other. Core needle biopsy yielded sufficient material for making reliable preoperative histopathological diagnosis. Of the six parameters studied, histological grade, hormone receptor expression and HER-2/neu overexpression correlated significantly with other parameters. Clinical stage correlated only with histological grade. Menopausal status did not correlate with any parameter.